Uncertainty and Sensitivity Analysis of Void Reactivity Feedback for 3D BWR Assembly Model. (25th October 2017) - Slavickas, Andrius; Pabarčius, Raimondas; Tonkūnas, Aurimas; Ušpuras, Eugenijus
Abstract : Uncertainty and sensitivity analysis of void reactivity feedback for 3D BWR fuel assembly model is presented in this paper. Uncertainties in basic input data, such as the selection of different cross section library, manufacturing uncertainties in material compositions, and geometrical dimensions, as well as operating data are considered. An extensive modelling of different input data realizations associated with their uncertainties was performed during sensitivity analysis. The propagation of uncertainties was analyzed using the statistical approach. The results revealed that important information on the code predictions can be obtained by analyzing and comparing the codes estimations and their associated uncertainties.